DEVELOPMENT OF STANDARDIZED OLFACTORY TEST AS A COGNITIVE IMPAIRMENT SCREENING TOOL IN INDONESIAN ELDERLY: A PRELIMINARY STUDY - Kristian, Kevin; Handajani, Yvonne Suzy; Widjaja, Nelly Tina; Suswanti, Ika; Turana, Yuda (Berkala Ilmiah Kedokteran Duta Wacana, 2024)
The decline of olfactory function is an early indicator of neurodegenerative diseases, such as Alzheimer’s and Parkinson’s disease. An olfactory function assessment instrument using ten familiar scents with multiple-choice answers has been developed, but several items were inapplicable and had not been standardized. This study aimed to identify various scents that have not been standardized for the aging population with normal cognitive function. This research was a preliminary study with a descriptive cross-sectional approach conducted in Kalianyar village, Jakarta, involving 23 elderly participants with normal cognitive function. An instrument consisting of a list of scents was employed in two steps, with or without assistance. Initially, participants had one chance to smell and try to guess the type of scent given. If the scent was not guessed correctly, participants were then provided with multiple-choice options as a hint. Based on the assessment of twelve scents from the existing research, only nine scents were recognizable. Among them, coffee, lemongrass, oranges, eucalyptus, and menthol were the scents with the most correct answers without assistance. Additionally, there were four scents recognized with or without assistance, such as jasmine, lemon, aromatic ginger, and lime. This study found that only nine scents were familiar and had the potential to be utilized in the future as a screening tool for cognitive impairment.